The behavioral immune system: Current concerns and future directions. Issue 2 (26th January 2018) - Ackerman, Joshua M.; Hill, Sarah E.; Murray, Damian R.
Abstract: The behavioral immune system is a motivational system that helps minimize infection risk by changing cognition, affect, and behavior in ways that promote pathogen avoidance. In the current paper, we review foundational concepts of the behavioral immune system and provide a brief summary of recent social psychological research on this topic. Next, we highlight current conceptual and empirical limitations of this work and delineate important questions that have the potential to drive major advances in the field. These questions include predicting the ontological development of the behavioral immune system, specifying the relationship between this system and the physiological immune system, and distinguishing conditions that elicit direct effects of situational pathogen threats versus effects that occur only in interaction with dispositional disease concerns. This discussion highlights significant challenges and underexplored topics to be addressed by the next generation of behavioral immune system research.